(3OhQ GdfjGHI GdYGeI ai MeGjI GdCSQI GdeUQjI ai VhA CMcGe Gdabg GdESdGei h bhGfjf GdCSQI (B: s (3OQGSI ebGQfI (B/ s - (3MSf YeQ MSf GdMSjfis; (3eMeO jhSa Mafi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2021)
(3JfGhdJ GdQSGdI ETcGdjI eOi eSGgeI JTQjYGJ GdCMhGd GdTNUjI h bhGfjf GdCSQI GdeJYGbHI ai OhQ GdfjGHI GdYGeI ai MeGjI hJjSjQ UYhHGJ GdJbGVi Ydi GdCSQI GdeUQjI h JMbjb GdUGdM GdYGe(B. (3h CXgQJ GdQSGdI GdOhQ GdbGfhfi ddfjGHI GdYGeI ai eLGd bGfhf GdCSQI ShGkA ai eLGd GdhdGjI Ydi GdfaS Ch GdhdGjI Ydi GdeGd(B: (3hGJNPJ ef GdbGfhf (B1(3dSfI (B2000 (3bGfhkfG eaUdkjG jaQb Hjf OhQgG bHd gPG GdbGfhf h HYOg(B. (3h ai YGe (B1996(3UOQ GdbGfhf Qbe (B3(3dSfI (B1996(3HTCf GdMSHI(B: (3h GdPi MUQ GdMb ai JMQjc OYhi GdMSHI h MaXgG Ydi GdfjGHI GdYGeI abW(B: (3h HQR OhQ GdfjGHI GdYGeI ai EScGf GdeMVhf h GdaUd ai GdefGRYGJ GdNGUI HeScf GdMVGfI h GdRhLjI(B. (3Ke UOQ GdbGfhf (B1 (3dSfI (B2000 (3h GdPi CVGa GNJUGUkG LOjOG ddfjGHI GdYGeI HTCf efGRYGJ MVGfI GdUZjQ; h CVGa GNJUGUG LOjOG ddfjGHI GdYGeI HTCf JMbjb ONd GdedJRe HGdfabI(B: (3cPdc CVGa GNJUGUG LOjOG dgG HMb GdfjGHI GdYGeI HGdUQa ef CehGd GdeTehd HGdMeGjI eHGTQI HbQGQ efgG Ohf GdQLhY ddeMceI(B. (3Ke UOQ GdbGfhf (B10 (3dSfI (B2004 (3bGfhf GdCSQI djfTF fjGHI GdCSQI PGJ GdGNJUGU GdfhYi HbVGjG GdCSQI(B: (3h CfGW HgG GdETQGa Ydi bde cJGH eMGce GdCSQI h OhGFQgG GdESJFfGajI h LYd JONdgG ai LejY bVGjG GdCSQI JONd h LhHi(B: (3h bUQ GdWYf HGdfbV Ydi GdfGFH GdYGe(B. (3h GfJgJ GdQSGdI HJhUjGJ HTCf EYGOI JQJjH GdeSJMbjf ddMVGfI(B: (3h cPdc EfTGA GdbVGA GdeSJYLd OGNd eMceI GdCSQI h GdfU Ydjg HbGfhf GdCSQI(B: (3h EYGOI GdWYf HGdfbV dHYV GdbVGjG eKd bVGjG GdfSH h bVGjG HWdGf EYdGe GdhQGKI(B: (3h Cf jchf JfajP bQGQ JSdje GdUZjQ GdUGOQ ef GdfjGHI GdYGeI HWQjb eZGjQ ddJfajP MGdjG eQGYGI ddbUO GdJTQjYi ef GdfU GdLOjOs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdTQjYI GdESdGejI, (B2021s
(3HHdjhLQGajG(B: (3UaMGJ (B365-381s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdTQjYI GdESdGejIs; (3CMcGe Gdabg GdESdGeis; (3GdfjGHI GdYGeI s; (3GdGOYGA GdYGes; (3GdGNJUGU GdbGfhfj ddfjGHI GdYGeI aj GdNUheGJ GdeOfjI s; (3SdWGJ GdfjGHI GdYGeI aj MeGjI GdCSQI s; (3OYhi GdMSHI s; (3eScf GdMVGfI s; (3Scfi GdeMVhf ef efXhQ Gdabg GdESdGej s; (3efGRYGJ GdMjGRI s; (3MjGRI eScf GdRhLjI s; (3GdMVGfI Hjf CMcGe Gdabg GdESdGej hGdbGfhf GdeUQjs; (3GdMb aj GdMVGfI s; (3GdCgdjI aj Gdabg GdESdGej hGdbGfhf GdeUQjs; (3GdNGVYjf dbGfhf GdhdGjI Ydi GdeGd s; (3GfJgGA GdhUGjI hQaY GdMLQ hEfgGA GdeSGYOI GdbVGFjI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdTQjYI GdESdGejIs